Features of drug-drug interactions rivaroxaban and calcium channel blockers depending on the ABCB1 genotype (rs1045642 and rs4148738) in patients 80 years of age and older with non-valvular atrial fibrillation - D. A. Sychev; K. B. Mirzaev; M. S. Cherniaeva; N. V. Shakhgildyan; Sh. P. Abdullaev; N. P. Denisenko; Zh. A. Sozaeva; A. A. Kachanova; V. R. Shastina; S. V. Gorbatenkova (Acta Biomedica Scientifica, 2024)
Background. The use of P-glycoprotein (P-gp) inhibitors and carriage of certain ABCB1 polymorphisms can lead to increased concentrations of rivaroxaban and the development of bleeding.The aim of the study. To study the features of drug-drug interactions (DDI) of rivaroxaban in patients over 80 years of age with non-valvular atrial fibrillation depending on the ABCB1 genotype (rs1045642 and rs4148738) using the example of verapamil (P-gp inhibitor) and amlodipine.Materials and methods. One hundred and twenty-eight patients were examined (median age – 87.5 [83–90] years). Genotyping, determination of the minimum equilibrium concentration of rivaroxaban (Cmin, ss), with standardization for the daily dose (Cmin, ss/D), coagulogram and analysis of medical documentation for the presence of clinically relevant non-major bleeding (CRNM) were carried out. Analysis of CRNM was performed depending on the ABCB1 genotype.Results. The use of rivaroxaban with verapamil in comparison with patients not taking calcium channel blockers (CCBs) leads to high Cmin, ss values in the CC genotype (rs1045642, rs4148738); Сmin, ss and Сmin, ss/D in the CT genotype (rs1045642); prothrombin time in the CC genotype (rs1045642), more frequent occurrence of CRNM in the TT  genotype (rs1045642, rs4148738). In  comparison with patients taking amlodipine, it leads to high Cmin, ss values in the CT genotype (rs1045642), a more frequent occurrence of CRNM in the TT genotype (rs1045642, rs4148738). The use of rivaroxaban with amlodipine in comparison with patients not taking CCBs leads to high Cmin, ss and Cmin, ss/D values in the CC genotype (rs1045642) (p < 0.017).Conclusion. The use of verapamil with rivaroxaban in ABCB1 TT carriers (rs4148738 and rs4148738) leads to the development of CRNM in 75 and 78 % of cases, respectively. In  patients taking rivaroxaban, it is advisable to test the ABCB1 genotype (rs4148738 and rs4148738) before adding a P-gp inhibitor to therapy.